PERAN CITRA MEREK MEMEDIASI KREDIBILITAS CELEBRITY ENDORSER TERHADAP NIAT BELI SMARTPHONE OPPO - Utami, Nyoman Tri Putri; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 7 No 6 (2018), 2018)
Along with the development of smartphone technology in Indonesia the higher competition among companies. Oppo smartphones are now on the market in Indonesia and are being intensively promoted using celebrity endorser. This study aims to determine the intention to buy using Oppo smartphones by using the credibility variable of endorser celebrities and variables of mediation. This research was conducted in Denpasar City by using sample size of 115 people with purposive sampling method. Data analysis technique used in this research is path analysis and test of sobel. The results showed. Significantly significant positive recruits to purchase intentions to use Oppo smartphones. The brand image is significantly capable of mediating the relationship between the celebrity endorser's credibility with the intention of buying an Oppo smartphone. Suggestions that can be used as a reference for companies and marketers who are expected to pay attention to the quality of well-prepared celebrities.